An Epistemic Characterisation of Extensive Form Rationalisability - Pierpaolo Battigalli; Marciano Siniscalchi (Fondazione Eni Enrico Mattei (FEEM), 1999)
We use an extensive form, universal type space to provide the following epistemic characterisation of extensive form rationalisability. Say that player i strongly believes event E if i is certain of E conditional on each of her information sets consistent with E. Our main contribution is to show that a strategy profile s is extensive form rationalisable if and only if there is a state in which s is played and (0) everybody is rational, (1) everybody strongly believes (0), (2) everybody strongly believes (0) & (1), (3) everybody strongly believes (0) & (1) & (2), .... This result also allows us to provide sufficient epistemic conditions for the backward induction outcome and to relate extensive form rationalisability and conditional common certainty of rationality.
Keywords: C7; 330; Rationalisability; Extensive Form Games; Spieltheorie; Wissenschaft; Theorie; Extensives Spiel